Spectroscopic study of solar transition region oscillations in the quiet-Sun observed by IRIS using the Si iv spectral line - Sangal K.; Srivastava A.K.; Kayshap P.; Wang T.J.; González-Aviles J.J.; Prasad A. (My University, 2025)
In this paper, we use the Si iv 1393.755 Å spectral line observed by the Interface Region Imaging Spectrograph (IRIS) in the quiet-Sun (QS) to determine the physical nature of the solar transition region (TR) oscillations. We analyse the properties of these oscillations using wavelet tools (e.g. power, cross-power, coherence, and phase difference) along with the stringent noise model (i.e. power law + constant). We estimate the period of the intensity and Doppler velocity oscillations at each chosen location in the QS and quantify the distribution of the statistically significant power and associated periods in one bright region and two dark regions. In the bright TR region, the mean periods in intensity and velocity are 7 min and 8 min, respectively. In the dark regions, the mean periods in intensity and velocity are 7 min and 5.4 min, respectively. We also estimate the phase difference between the intensity and Doppler velocity oscillations at each location. The statistical distribution of the phase difference is estimated, which peaks at-119° ± 13°, 33° ± 10°, 102° ± 10° in the bright region and at-153° ± 13°, 6° ± 20°, 151° ± 10° in the dark regions. The statistical distribution reveals that the oscillations are caused by propagating slow magneto-Acoustic waves encountered with the TR. Some of these locations may also be associated with standing slow waves. Moreover, in the given time domain, several locations exhibit the presence of both propagating and standing oscillations at different frequencies. © 2022 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.